PREOPERATIVE RISK ASSESSMENT IN PEDIATRIC ANESTHESIA - Vlajković Ivanović, Ana; Pjevalica Dragić, Jelena; Simić, Dušica (Medical Research, 2024)
In the general pediatric surgical population the incidence of perioperative 30-day mortality is low. The child’s physical status at the time of elective surgery and the presence of comorbidities can notably impact on the perioperative risk. In order to provide quality care, preoperative evaluation should be undertaken in a timely and thorough manner.In the preoperative period it is highly important to be able to identify which patients are at higher risk, with the premise that early identification of these patients will allow for additional care to be provided, thereby minimizing the potential for complications. The main objectives of adequate preoperative assessment are to evaluate patient readiness for the procedure, optimize health status before surgery, reduce the morbidity of surgery and return the patient to their usual function postoperatively. The routinely prescription of additional tests in children should be replaced by a selective and rational prescription, based on the patient history and performed clinical evaluation. Surgical and anesthesia complications can have adverse effects on the patient’s health, and also have been shown to be associated with increased inpatient and postoperative costs. Each member of the surgical team plays a vital role in the safe care of the pediatric patient.  Well known risk factors for critical events in the perioperative period in the pediatric population are: ASA physical status, age, emergency surgery and the existence of an underlying disease.This review highlights the potential risks encountered in the children and directs the preoperative assessment towards selecting essential tests based on identified individual risk factors.Keywords: anesthesia, pediatrics, preoperative testing, risk factors